Haploidentical hematopoietic stem cell transplantation for pediatric Philadelphia chromosome-positive acute lymphoblastic leukemia in the imatinib era. (August 2017) - Chen, Huan; Liu, Kai-yan; Xu, Lan-ping; Chen, Yu-hong; Zhang, Xiao-hui; Wang, Yu; Qin, Ya-zhen; Liu, Yan-rong; Lai, Yue-yun; Huang, Xiao-jun
Highlights: Allo-HSCT remains an important curative option for children with Ph+ ALL. The role of HID HSCT in pediatric patients with Ph+ ALL has not been reported. The 5-year EFS and OS were 61.0% and 70.0% in HID HSCT for children with Ph+ ALL. The 3-year incidence of relapse and non-relapse mortality were 22.7% and 16.4%. BCR-ABL positivity on +30 day post-HSCT was a significant factor for relapse. Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains an important curative option for children with Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL) who have a poor response to chemotherapy plus imatinib. For such children, if there are no matched related or unrelated donors, alternative donor transplantation may be a choice. The role of haploidentical donor (HID) HSCT in pediatric patients with Ph+ ALL has not been reported. The study population included pediatric patients with Ph+ ALL who underwent HID-HSCT. BCR-ABL transcript levels were analyzed using real-time quantitative reverse transcription polymerase chain reaction. At a median follow-up of 34 months, the 5-year probabilities of event-free survival (EFS) and overall survival (OS) were 61.0% and 70.0%, respectively in HID HSCT. The 3-year incidence of relapse and non-relapse mortality was 22.7% and 16.4%. Multivariate analysis showed that the post-HSCT BCR-ABL transcript level on +30 day was a significant factor affecting relapse rate. HID HSCT for the treatment of pediatric patients with Ph+ ALL yielded promising long-term survival. Post-HSCT BCR-ABL transcript positivity was a significant factor for clinical relapse after allo-HSCT in the imatinib era.